Guidelines for UiTM branch campuses: library buildings concept towards a Digital Library / Faridah Talib - Talib, Faridah (2001)
This study is aimed to identify and thus provide a standard guideline to PTAR management for the digital library building to be implemented at the branch campuses and the faculty level. The project brief that consists of some basic principles on the specific requirements of the client on the library building, will be submitted to both the Strategic Planning Unit of UiTM and the appointed Architect for further action. This is to ensure that, it could be implemented to all the branch and faculty libraries of UiTM. The paper also suggests guidelines to build an intelligent library building, equipped with necessary infrastructure that is suitable for a digital / electronic library. Here, it focuses on the infrastructure of the technological capabilities suitable for current and future equipment needs; and also in creating a network that will expand access beyond the library apart from providing a plan for a new building that will serve the university for at least twenty years. These needs arise due to a lack of a standard guideline in the planning and building of UiTM library building for the branch campuses and faculty libraries throughout Malaysia. Furthermore, the Librarians from the branch campuses often face problems of having to renovate certain interior/exterior part of the building, (i.e. after the library building has been fully completed and handed-over to the client). This results from the improper planning of the library building at the initial stage and thus has incurred unnecessary cost to UiTM.